CEU Opening Ceremony 2004
Recording of the CEU Opening Ceremony for the academic year 2004/2005, held on September 24, 2004 at the CEU Residence and Conference Center. The students are welcomed by Academic Pro-Rector László Mátyás who is also the Master of Ceremonies. The opening remarks are delivered by Yehuda Elkana, President and Rector of CEU. The Student Speaker greeting the fellow students is Nicole Gallagher a newly enrolled student at the International Relations and European Studies Department at CEU. The Alumni Speaker is Lívia Járóka, an MA Graduate from the CEU Department of Sociology in Warsaw. Her speech is followed by the opening address delivered by Josef Jařab, former CEU President and Rector and at the time being Senator of the Czech Parliament. After a brief musical interlude, Prof. János Kornai is awarded the Honorary Doctorate. The “laudatio” is delivered by the Head of the Department of Economics, Prof. Ugo Pagano while the awarding of the honorary doctorate in the name of the Senate of the University is being done by Yehuda Elkana. The awarding is followed by János Kornai’s public lecture. The ceremony ends with László Mátyás’ closing remarks.